2020
DOI: 10.1186/s40463-020-00453-2
|View full text |Cite
|
Sign up to set email alerts
|

Definitive surgical management for second branchial cleft fistula: A case series

Abstract: Background Second branchial cleft fistulae are rare pediatric anomalies managed with surgical excision and, in certain cases, ipsilateral tonsillectomy to prevent postoperative recurrence or wound infection. Limited information is available in the published literature regarding surgical techniques to maximize patient outcomes and minimize recurrence. Our objective was to describe outcomes for the largest series of branchial cleft fistulae excised using a uniform technique based on embryologic prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…This obviates the need for ipsilateral tonsillectomy and also lowers the recurrence rate. 26,27 Histology often reveals turbid yellow fluid containing cholesterol crystals and stratified squamous epithelium linig. 3 Complications of surgery include, recurrence, mostly due to incomplete surgical excision, which could be 3% in fresh cases and up to 20% in second surgical attempts.…”
Section: Case Reportmentioning
confidence: 99%
“…This obviates the need for ipsilateral tonsillectomy and also lowers the recurrence rate. 26,27 Histology often reveals turbid yellow fluid containing cholesterol crystals and stratified squamous epithelium linig. 3 Complications of surgery include, recurrence, mostly due to incomplete surgical excision, which could be 3% in fresh cases and up to 20% in second surgical attempts.…”
Section: Case Reportmentioning
confidence: 99%
“…Several recent studies have found that performing a tonsillectomy confers no additional clinical benefit and should be avoided. 48,54,55 Endoscopically-assisted dissection techniques obviate the need for additional incisions and reduce the morbidity of surgery. 56 Guerrissi 57 was the first to describe this technique and demonstrated excellent visualization of a second BCA fistulous tract through a minimal skin incision.…”
Section: Second Branchial Cleft Anomaliesmentioning
confidence: 99%
“…Several recent studies have found that performing a tonsillectomy confers no additional clinical benefit and should be avoided. 48,54,55…”
Section: Introductionmentioning
confidence: 99%
“…To prevent any risk recurrence the surgeon must make sur the excision is complete. An ipsilateral tonsillectomy ensures removal of the fistulous tract [10]. But it is not required, as some studies have shown, to avoid recurrences [11].…”
Section: Case Reportmentioning
confidence: 99%